1992
DOI: 10.1111/j.1472-765x.1992.tb00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age on ergosterol content in mycelium of Aspergillus ochraceus

Abstract: Ergosterol has been suggested as a paramoter for studying the content and evolution of fungal infestation in different products. Important differences in this parameter have been described for different genera and species. A study of the relationship between ergosterol content and dry mass in a strain of Aspergillus ochraceus, which is able to produce an antifungal agent, has therefore been carried out in order to use this parameter to accurately evaluate the fungal mass of this strain. We report herein our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The differences between the formation of this sterol and growth of mould involved the fact that in the stationary phase the reduction in the level of ergosterol in the mycelium occurred earlier than the reduction in the quantity of dry mass. Torres et al. (1992) also noted in his investigations that ergosterol content varied with the age of the culture differently than mycelium biomass.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The differences between the formation of this sterol and growth of mould involved the fact that in the stationary phase the reduction in the level of ergosterol in the mycelium occurred earlier than the reduction in the quantity of dry mass. Torres et al. (1992) also noted in his investigations that ergosterol content varied with the age of the culture differently than mycelium biomass.…”
Section: Discussionmentioning
confidence: 89%
“…The differences between the formation of this sterol and growth of mould involved the fact that in the stationary phase the reduction in the level of ergosterol in the mycelium occurred earlier than the reduction in the quantity of dry mass. Torres et al (1992) also noted in his investigations that ergosterol content varied with the age of the culture differently than mycelium biomass. Mille-Lindblom et al (2004) confirmed in their investigations a significant 34% degradation in ergosterol in mycelium after the death of fungi, the degradation being greater in case of additional action of light.…”
Section: Discussionmentioning
confidence: 89%
“…At nitrogen concentrations of 0.5 -0.9 g/1 of different amino acids, the production of lanosterol (R,:0.5) was inhibited, but at 0. [25].…”
Section: Triterpenesmentioning
confidence: 99%
“…Mille-Lindblom et al ( 2004 ) showed that it underwent significant degradation (43 %) under the action of light. Also ergosterol synthesis has been found to be significantly influenced by phase of moulds growth, ageing, and environmental parameters (media, pH, temperature) (Torres et al 1992 ; Gutarowska and Żakowska 2009 ). Studies have shown that on the death of mould the ergosterol content may fall by as much as 34 % (Mille-Lindblom et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%